Coating induced corrosion of coronary stents - A comparative study with clinical consequences - Navarro, Lucila (2020)
The clinical failsof gold (Au) and carbon (C) coated 316LSS stents have been barelyinvestigated. A comprehensive understanding of these fails maycontribute to the improvement of protocols for the development ofbetter materials and surfaces. This work elucidates the reasons ofthe clinical fails of Au and C coated 316LSS stents, demonstratesthe physical-chemical processes that leaded to these fails, reviewsthe mistaken line of thought that pushed these technologies to themost advanced clinical stages and proposes complementary techniquesto the FDA guidances for the early non-clinical engineering tests. Auand C coated 316LSS, bare-metal 316LSS and Co-Cr stents were studiedusing potentiodynamic scans according to FDA guidance protocols,image analysis and bulk elemental composition. The statisticalclinical outcome of the stents was found to correlate with the ionsrelease patterns eluted from their corresponding metallic substrates.In all cases ions release were consequence of post-passive corrosionprocesses such as pitting corrosion of 316LSS and bulk graindissolution of Co-Cr alloy. Surprisingly, the stents outcome did notcorrelate with their corresponding corrosion rates. Clinical fails ofAu and C coated 316LSS stents are explained in terms of their failsto inhibit the ions release from their 316LSS substrates. Materialsand surface improvements must be oriented to inhibit post-passivecorrosion processes of stents substrates. Potentiodynamic scanscomplemented with image analysis are strongly recommended for theevaluation of pre-clinical engineering tests.